Genetic Variability in the Germplasm of Mehndi (Lawsonia inermis) - Singh, Manjit; Jindal, S K; Sivadasn, Rekha (Annals of Arid Zone, 2016)
Lawsollia illermis Linn., a dye yielding perennial shrub, is commonly known as mehndi or henna. Cuttings from 20 shrubs selected on the basis of high leaf yield, minimum flowering and fruiting, free from insect pests, etc., were collected from different sites of Rajasthan and Gujarat and evaluated in RBD with three replications. There were significant differences for plant height, plant spread, primary branches, fresh biomass, dry leaf yield and dry stem weight per plant except lawsone content. Accession Dhandhuka has been found to contain maximum lawsone content per plant and for immediate gains this accession can be multiplied at large scale and distributed to the farmers. Key words: Lawsollia illermis Linn., genetic variability, germplasm improvement.